Kedudukan Islam Dalam Sistem Ketatanegaraan Indonesia - Asiyah; Musaddad Al Basry; Fakinah Herliani; Mubarik; Absor (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract The relegion of Islam in Indonesia has been around for a long time since Islam came to Indonesia. Since then, Islam has taken root in Indonesian society. The coming of the Netherlands to Indonesia, although initially acknowledging the existence of Islamic law in the community, has been hampered in its development due to the interests of colonialism. Efforts to restore the position of Islam continued before and after independence. The Indonesian constitutional system relies on Pancasila and the 1945 Constitution. The ideology of Pancasila rests on the Almighty God, and this indicates that there is an obligation on the part of the Indonesian people to carry out God's commands according to Islam to apply Islamic shari’a. Thus Islamic law has a position in the national legal system and can contribute to the development of national law. Keywords: Islam, Constitutional System, Indonesia